T-cell Lymphoblastic Leukaemia/Lymphoma Presenting as Bilateral Renal Enlargement and Arthritis: A Rare Case Report - Bhuiyan, Md Minhaj Uddin; Bhowmic, Rajib; Siddiki, Md Shahriar; Patwari, Md Kamrul Hasan; Biswas, Sarmistha (Journal of Medicine, 2020)
Lymphoma usually presents as painless enlargement of lymph nodes with or without systemic symptoms like fever, weight loss, night sweats, itching and hepatosplenomegaly. But renal enlargement and arthritis as initial manifestations of lymphoma are very uncommon and poses a potential diagnostic challenge. Renal manifestations of lymphoma are usually nonspecific hematuria, fever, flank pain and oliguria. Pathological data are scanty in this regard; few reports indicate that it has a very poor prognosis. Here we described a case of lymphoma presented with bilateral palpable kidneys, pyrexia and arthritis. Initially diagnosis was confused as renal dysfunction was absent and also the condition is rare. However, strong clinical suspicion along with radiological and histopathological evidence as well as immunophenotyping tests helped to diagnose the case as T-cell lymphoblastic leukaemia/lymphoma. J MEDICINE JUL 2020; 21 (2) : 109-112